What factors are associated with dental general anaesthetics for Australian children and what are the policy implications? A qualitative study - John Rogers; Clare Delany; Clive Wright; Kaye Roberts-Thomson; Mike Morgan (BMC, 2018)
Abstract Background Dental general anaesthetics undertaken on young children are amongst the most common of all potentially preventable hospitalisations of children in Australia. They are costly for families and the community and entail some risk. The aim of the study was to explore the views of stakeholders about factors associated with children's dental general anaesthetics in Victoria, Australia and to identify policy implications. Methods Interviews with stakeholders were used to develop a framework of factors. Interview data were subject to qualitative analysis, informed by Interpretative Phenomenological Analysis. Results Eight themes that encompassed 30 main factors were identified through focused discussions with 16 stakeholders. While the safety of dental general anaesthetics has improved and mortality rates are low, side effects are common. Push factors for children's dental general anaesthetics include a perceived greater 'child-focus'; preferred models of care; low oral health literacy; parent guilt; convenience; and some dentists reluctance to treat high needs children in the clinic. Factors that may decrease the prevalence of dental general anaesthetics include: prevention of dental caries; using alternative approaches; an appropriate workforce mix; enhancing oral health literacy; and development of guidelines. Conclusion The prevalence of hospitalisation of children to treat dental caries is increasing. Many factors influence the prevalence of paediatric dental general anaesthetics - relating to the child, parent, oral health professional, financial impact, health risk, and accessibility to facilities. There are quality of care and convenience benefits but also high costs and possible health risks. Family, workforce and health system factors have been identified that could decrease the prevalence of paediatric dental general anaesthetics.